ROLE OF PARENTS IN IMPROVING GEOGRAPHY LEARNING MOTIVATION IN IMMANUEL AGUNG SAMOFA HIGH SCHOOL - Beatus Mendelson Laka; Jemmi Burdam; Elizabet Kafiar (Sekolah Tinggi Pariwisata Mataram, 2020)
Basically the role of parents is more important than the role of a teacher. This is because the first and foremost education is in the family, the child's character's parents. In addition, parents have a lot of time with children from the teacher. Therefore, the role of people is very important for children in providing motivation. Whereas the teacher has very limited time with children because only during school hours. The formulation of the problem in this study is how the role of parents in increasing motivation to learn geography in Immanuel Agung Samofa High School. The purpose of this study was to determine the role of parents in increasing student motivation. This type of research is a type of qualitative research. The method used in this research is interview, questionnaire and documentation. Data analysis techniques in the form of qualitative analysis. The results of this study show that the parents of students at Immanuel Agung Samofa High School have not been maximal in providing motivation for children, this is seen when the teacher checks the learning equipment in the form of stationery, then the presence of students in class during geography learning hours takes place students play, often in and out and often do not take the lesson seriously. as the first teacher for children and parents also who understand more